Fear-Potentiated Startle and Fear Extinction in a Sample of Undergraduate Women Exposed to a Campus Mass Shooting - Orcutt, Holly K.; Hannan, Susan M.; Seligowski, Antonia V.; Jovanovic, Tanja; Norrholm, Seth D.; Ressler, Kerry J.; McCanne, Thomas (Frontiers in Psychology, 2017)
Posttraumatic stress disorder (PTSD) is a common psychological disorder that affects a substantial minority of individuals. Previous research has suggested that PTSD can be partially explained as a disorder of impaired fear inhibition. The current study utilized a previously validated fear acquisition and extinction paradigm in a sample of 75 undergraduate women who were exposed to a campus mass shooting that occurred in 2008. We used a protocol in which conditioned fear was first acquired through the presentation of one colored shape (reinforced conditioned stimulus, CS+) that was paired with an aversive airblast to the larynx (unconditioned stimulus, US) and a different colored shape that was not paired with the airblast (non-reinforced conditioned stimulus, CS−). Fear was extinguished 10 minutes later through repeated presentations of the CSs without reinforcement. Number of clinically significant posttraumatic stress symptoms (PTSS) immediately following the mass shooting were positively associated with fear-potentiated startle (FPS) to the CS+ and CS- during late periods of acquisition. During early periods of fear extinction, PTSS was positively associated with FPS to the CS+. Results from the current study suggest that PTSS is related to altered fear inhibition and extinction during an FPS paradigm. In line with similar research, women with greater PTSS demonstrated a greater “fear load,” suggesting that these women experienced elevated fear to the CS+ during extinction after conditioned fear was acquired.